Numerical Implementation of an Additive Strain Model for the Damage Simulation of Fatigue-Loaded Concrete - Dennis Birkner; Steffen Marx (International Journal of Concrete Structures and Materials)
Abstract Investigating the fatigue behavior of concrete structures from wind turbine towers is associated with major challenges due to the high number of occurring load cycles and large cross-sectional dimensions. Thus, only few studies have been carried out on concrete structures subjected to cyclic bending loads. Numerical simulations, in contrast, enable fast investigations of many parameter variations. There are many material models available for different applications, yet they quickly become very complex and require time-consuming calibration of input parameters in structural tests. A model for simulating macroscopic damage processes in fatigue-loaded compressed concrete cross sections, which can be calibrated using standard cylinder tests, does not yet exist. The present work aims to close this gap and implements an additive strain model to simulate the strain and damage development of concrete subjected to fatigue bending loads. Therefore, experimental investigations were designed and carried out. Static and cyclic tests on concrete cylinders yielded the input parameters for the material model. A strain model was implemented in ANSYS Mechanical. The numerical implementation was validated using fatigue tests on large prestressed beams in a resonance-based testing facility. The beam specimens mostly failed due to fatigue in the compression zone. The numerical model confirmed the effects observed in the beam tests and was able to simulate the most damaged regions very well. Moreover, stress redistribution to less loaded regions as a result of relief of the damaged regions was detected. This confirmed the positive effect of stress redistributions on the fatigue life of the structures.